Respuesta :
first divide both sides by 2
x³-6x²=16x-96
minus 16x from both sides and dd 96 to both sides
x³-6x²-16x+96=0
factor by grouping
(x³-6x²)+(-16x+96)=0
(x²)(x-6)+(-16)(x-6)=0
undistribute the (x-6)
(x²-16)(x-6)=0
(x-4)(x+4)(x-6)=0
set each to zero
x-4=0
x=4
x+4=0
x=-4
x-6=0
x=6
x=-4, 4, and 6
x³-6x²=16x-96
minus 16x from both sides and dd 96 to both sides
x³-6x²-16x+96=0
factor by grouping
(x³-6x²)+(-16x+96)=0
(x²)(x-6)+(-16)(x-6)=0
undistribute the (x-6)
(x²-16)(x-6)=0
(x-4)(x+4)(x-6)=0
set each to zero
x-4=0
x=4
x+4=0
x=-4
x-6=0
x=6
x=-4, 4, and 6